HUKUM SENTUHAN KULIT (JABAT TANGAN) - Dahliati Simanjuntak (Institut agama islam negeri Padangsidimpuan, 2020)
One of the many problems faced by the community, is the problem of shaking hands with men, especially with non mahram relatives.now days, the handshake between men andwomen who are not mahram is almost a custom and tradition that is considered very advanced.more so on holidays, gatherings and the like. this we see a lot of televisionand sometimes even accompanied by kisses and hugs. they have followed western traditions and imitated their lifestyles.